Sistema de tomada de decisão de controle de bemisia tabaci em cultivos de melancia - Lima, Carlos Henrique de Oliveira (Universidade Federal do Tocantins, 2018)
The watermelon Citrullus lanatus (Thunb.) Matsum & Nakai belonging to the cucurbit family has been extensively explored since the beginning of agriculture. The fruit has great commercial importance because of the great appreciation for its fleshy, succulent and sweet fruits and the value paid by them. The cultivation of the fruit in 2014, occupied an area of 3.48 million hectares in the world, reaching a production of about 222 million tons. Despite being heavily exploited and the strong economic appeal, several factors of losses that affect the watermelon culture. Among these loss factors, the whitefly Bemisia tabaci (Genn.) (Hemiptera: Aleyrodidae) is cited as an important and high-potential pest causing losses in fruit production mainly by the transmission of plant-causing viruses, such as Begomovirus and Carlavirus. Losses of up to 100% due to diseases transmitted by B. tabaci are reported. Therefore, studies that evaluate the interaction of the pest with the plant that accurately reflect the reality of agroecosystems is very important to determine sampling plans and forecasting models that assist in integrated pest management and assist in the decision making process. Thus, in this study aimed to determine the dispersion pattern of B. tabaci, colonization habits correlating this with climatic and biological factors. These studies determine that sampling of adults of B. tabaci in watermelon crops should be performed by counting directly on the 6th most apical leaf of the branches. The populations of B. tabaci presented a high degree of spatial dependence and the range of colonization was up to 20 m. The rainfall intensity as well as the populations of Eriopis connexa (Coleoptera: Coccinellidae) and Chrysoperla sp. (Neuroptera: Chrysopidae) negatively affected the populations of B. tabaci. The estimated economic damage levels for B. tabaci in this crop considering the stages of development of the plant were 0.52, 0.21 and 0.13 insects per sample for the vegetative phase and 1.69, 0.69 and 0 , 44 insects per sample for the reproductive phase when fruit prices were low, medium and high, respectively.